A systematic interim assessment of the Australian Government's Food and Health Dialogue. Issue 2 (3rd February 2014) - Elliott, Tamara; Trevena, Helen; Sacks, Gary; Dunford, Elizabeth; Martin, Jane; Webster, Jacqui; Swinburn, Boyd; Moodie, A Rob; Neal, Bruce C
Abstract: Objective: To evaluate whether the Food and Health Dialogue (the Dialogue), established by the Australian Government in 2009, is having an impact on reducing premature death and disability caused by poor diet in Australia. Design and setting: We used information derived from the Dialogue website, media releases, communiqués and e‐newsletters to evaluate the Dialogue's achievements from October 2009 to September 2013, using the RE‐AIM (reach, efficacy, adoption, implementation and maintenance) framework. Data describing the processed foods marketed in Australia were extracted from an existing food composition database. Main outcome measures: Achievements of the Dialogue (goals, targets, actions and health outcomes). Results: The primary goal of the Dialogue was identified as "raising the nutritional profile of foods" to be achieved "through reformulation, consumer education and portion standardisation". Employing a public–private partnership model, the Dialogue has established a framework for collaboration between government, public health groups and industry. In the first 4 years, targets were set for 11 (8.9%) of a total of 124 possible action areas for food reformulation and portion standardisation. None were yet due to have been achieved. There was no evidence that any education programs had been implemented by the Dialogue. There are no indicators of the extent to which population exposure to target nutrients has changed or whether any positive or negative health impacts have ensued. Conclusions: The Dialogue has highly creditable goals but the mechanism for delivering on them has proved inadequate. Explicit processes and the outcomes to be delivered within defined timelines are required, along with a clear plan for remediation if they are not achieved.